P-014 Venous sinus pulsatility in manometry evaluation of dural sinus narrowing in idiopathic intracranial hypertension. (12th July 2011) - Lazzaro, M; Zaidat, O; Darkhabani, Z; Fitzsimmons, B
Abstract : Introduction: Idiopathic intracranial hypertension (IIH) remains a poorly understood and therapeutically challenging disease. Enthusiasm has emerged for endovascular therapy with stent reconstruction of dural sinus narrowing, however a complete understanding of the hydrodynamic dysequilibrium is lacking. Few reports have characterized catheter manometry findings and none have addressed the pulsatility of the venous sinuses in IIH. Methods: We reviewed all cases of patients referred for endovascular evaluation of medically refractory IIH. Patients with venous sinus pulsatility attenuation after stent implantation were identified. Chart and imaging review was performed. Results: Two patients were identified with transverse sinus narrowing who underwent stent implantation with demonstrable attenuation of high venous pulsatility. Both cases demonstrated high pressure gradient across the focal narrowing (>30 mm Hg) and >70% stenosis. Mid-term follow-up revealed persistent clinical improvement. Conclusions: We report the finding of high venous sinus pulsatility attenuation after stent implantation for dural sinus narrowing and propose the hypothesis that this finding is a marker of advanced dural sinus incompetence. This characteristic may be useful in identifying patients who would benefit from endovascular stent remodeling.